Classification of Malicious Document Detection Based on Artificial Intelligence - Wang, Xingyu (International Journal of Computer Science and Information Technology, 2024)
Malicious document attacks are one of the severe threats in the current field of cybersecurity. This paper compares traditional and artificial intelligence methods in detecting malicious documents and proposes an application and technical framework of artificial intelligence in malicious document detection (AI-DDNet). First, it introduces various methods of malicious file attacks, including malicious code attacks, object embedding attacks, document vulnerability attacks, and remote link attacks. Then, it systematically elaborates on traditional static and dynamic analysis methods, as well as static and dynamic analysis techniques integrated with artificial intelligence, including machine learning, deep learning, and reinforcement learning. Lastly, it summarizes the challenges and unresolved issues of current technology and looks forward to the future development direction of artificial intelligence in malicious document detection. Through this study, it promotes the innovation and development of cybersecurity technology.